The effect of competence, independence and discipline on performance with job satisfaction as an intervening variable in the internal government supervisory apparatus (APIP) of the regional inspectorate throughout the Riau Islands Province - Auzar, Auzar; Ngaliman , Ngaliman (Global Academy of Business Studies, 2024)
Purpose: This study aimed to analyze the influence of competence, independence, and discipline on job satisfaction and employee performance, the effect of job satisfaction on performance, and the indirect influence of competence, independence, and discipline on performance through job satisfaction as an intervening variable at the APIP Regional Inspectorates in Riau Islands Province. Research methodology: Data were collected through questionnaires, observations, and documentation. The sample consisted of APIP employees from Regional Inspectorates across the Riau Islands Province. Data were analyzed using path analysis and hypothesis testing to examine the direct and indirect relationships among the variables. Results: The findings revealed that competence, independence, and discipline significantly enhanced job satisfaction and performance, with job satisfaction directly influencing performance and mediating their indirect effects, thereby strengthening overall employee outcomes. Conclusions: Competence, independence, and discipline drive job satisfaction and performance, while job satisfaction directly impacts and mediates performance. Limitations: This study is limited to the APIP Regional Inspectorates in the Riau Islands Province; therefore, generalization to other regions or institutions should be approached with caution. Contribution: This study provides empirical evidence for policymakers and management in government institutions, highlighting the importance of competence, independence, and discipline in enhancing job satisfaction and performance, with job satisfaction serving as a strategic mediating factor.